Public expenditures and the production of education - Neely, Stephen R.; Diebold, Jeffrey (Education Policy Analysis Archives, 2016)
The relationship between public education expenditures and student outcomes remains an important concern for policy analysts, educational administrators, and the public at large. While previous studies have failed to identify a consistent relationship between public investments in education and positive student outcomes, most analyses have not accounted for the different educational goals associated with various instructional expenditure categories. This study builds on prior research by using Pennsylvania’s public school districts to test proposed improvements in model specification for the traditional education production function. Using longitudinal, fixed-effects models, a detailed disaggregation of instructional expenditures is undertaken in order to account for the likelihood that different instructional subcategories (i.e. regular programming, special education, and vocational instruction) influence student outcomes in varying ways. The results suggest that the impact of expenditures may be understated in previous studies based on a failure to account for these distinctions, particularly in the case of Mathematics education.